Research on the high-accuracy mileage statistics method based on the civil satellite data - Zunmin Liu; Chuijie Yi; Zhihong Liu; Xilong Zhang (International Journal of Distributed Sensor Networks)
For the current situation of the large error in civil satellite positioning data resulting in the calculation of smaller mileage by the polyline method than the actual mileage, a new method of mileage statistics has been proposed in this article. First, the original trajectory data are preprocessed to eliminate data errors. Second, based on the principle of shape approximation, it is preferred to implement the quadratic B-spline curve to accurately fit the mileage trajectory curve, comparing various curve fitting methods. Then, based on the trajectory curve control point data, the mileage statistics formula is derived, and the accurate mileage statistics method for non-precision satellite positioning signals is realized. Finally, the road test is carried out by using the photoelectric non-contact five-wheel instrument and GPS equipment. The polyline method and curve fitting method are used to generate contrastive curve and calculate the mileage, respectively. Taking photoelectric five-wheel data as the accurate mileage, the error analysis is carried out. The results show that the deviation between calculated and actual mileage values is less than 1%. Therefore, this method can meet the user’s requirements for fleet management.